Economic Sustainability of the Australian Grain Supply Chain Post Market Deregulation - Krezel, Stephanie (European Journal of Sustainable Development, 2017)
From a grain supply chain once supported by a statutory market scheme, poised to stabilise market fluctuations and protect primary producer financial returns, the Australian grain market has now been significantly altered through the process of market deregulation. The deregulation of the Australian grain statutory market scheme created free market conditions in order to increase competition and industry growth; however removed much of the stabilisation mechanisms for primary producers and the greater grain supply chain. In opposition to the intent of the market deregulation, productivity growth within the primary production portion of the Australian grain supply chain has been notably diminished, since the deregulation of the statutory market scheme. Through understanding the impact of deregulation on the social systems, within the primary production environment of the Australian grain supply chain, it is evident that deregulation has had a significant effect on the capacity and desire of primary producers to innovate and the subsequent ability of the supply chain and grain industry to ensure economic sustainability. Keywords: Economic sustainability, supply chain, deregulation, grain production, risk, decision making